The effect of adding angkak as a substitute for saltpeter in the production of se'i beef with different storage durations - Sabtu, Bastari; Suryatni, Ni P. F.; Nepa, Juliana M. (Fakultas Peternakan Universitas Papua, 2025)
This study aimed to evaluate the physicochemical and microbiological quality of beef se’i produced with angkak extract as a natural saltpeter substitute at different storage durations. A factorial Completely Randomized Design (CRD) was applied, consisting of five angkak concentrations (0%, 1%, 1.5%, 2%, and 2.5%) and four storage durations (3, 5, 7, and 9 days). The measured variables included pH, total plate count (TPC), presence of Escherichia coli, and color characteristics. Data on pH and TPC were analyzed using ANOVA followed by Duncan’s test, color evaluation used the Kruskal–Wallis test, and E. coli was analyzed qualitatively. The interaction between angkak concentration and storage duration significantly affected pH, TPC, and color (P < 0.05) and suppressed E. coli growth. Increasing angkak levels and longer storage duration resulted in higher pH values and lower bacterial counts, indicating better preservation potential. Color scores decreased with higher angkak concentrations and longer storage time, although acceptable sensory characteristics were maintained until the fifth day of storage. No E. coli contamination was detected in any treatment. In conclusion, angkak extract shows promising potential as a natural alternative to saltpeter in the production of beef se’i, improving preservation, controlling microbial growth, and maintaining acceptable product quality.